Daily Life Experiences of Patients With a High-Grade Glioma and Their Caregivers: A Longitudinal Exploration of Rehabilitation and Supportive Care Needs. Issue 5 (October 2015) - Piil, Karin; Juhler, Marianne; Jakobsen, Johannes; Jarden, Mary
Abstract : ABSTRACT: Background: There is a lack of knowledge regarding the breadth of needs for rehabilitation and supportive care across the disease and treatment trajectory for patients with a high-grade glioma (HGG) and their caregivers.Objective: The aim of this study was to elucidate the experiences and needs for rehabilitation and supportive care in patients with HGG and their caregivers.Methods: Patients with malignant glioma ( N = 30) and their caregivers ( N = 33) were interviewed five times during the first year of the HGG trajectory. A thematic analysis of interviews at five time points revealed five main themes describing the experiences related to the illness trajectory and needs for rehabilitation and supportive care.Results: The five main themes identified were (a) individual strategy for acquiring prognostic information, (b) shared hope, (c) engagement in health promotion activities, (d) adjustment to symptom limitations, and (e) role transition from family member to caregiver.Conclusion: The individual and sometimes opposing preferences among patients and their caregivers for prognostic information is a chosen strategy that supports individual needs in managing the HGG trajectory. Patients and caregivers experience a feeling of solidarity, from which shared hope arises; however, this hope needs to be supported by healthcare professionals. Driven by hope, they seek to optimize the therapeutic effect of the oncological treatments by being engaged together in health promoting activities. As symptoms progressed, the need for information and guidance regarding symptoms and supportive care interventions became evident. Caregivers play a significant supporting role for the patients and need special support themselves and practical assistance especially when symptoms progress. Finally, there is a need for rehabilitation programs that target the cognitive ability of the patients to participate actively.